Rice Bran Particulates Reinforced Ipomoea Carnea Fiber Epoxy Composite for Engineering Application - Thandavamoorthy Raja; Vinayagam Mohanavel; Sathish Kannan; Vipul Vekariya; Dipen Paul; Palanivel Velmurugan; Arunachalam Chinnathambi; Sulaiman Ali Alharbi; Subpiramaniyam Sivakumar (Journal of Natural Fibers)
In the pursuit of sustainable and environmentally friendly engineering materials, this study investigates the potential of Ipomoea carnea fibers (ICF) as a reinforcement agent in bran particulates epoxy matrix used to fabricate the composite laminates by a traditional process with varying filler weight fraction. The composite material’s characteristics were comprehensively analyzed using various techniques, including X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Mechanical Testing, Scanning Electron Microscopy (SEM), and Thermogravimetric Analysis (TGA). The results of this study reveal the promising potential of Ipomoea carnea fibers reinforced bran particulates epoxy composite as a novel engineering material. The analysis indicates improved mechanical properties such as tensile, flexural, and impact strength, enhanced thermal stability, and desirable morphological characteristics. Subsequently, the structural and chemical properties of the Ipomoea carnea fiber composite were explored using XRD and FTIR, shedding light on the crystalline nature (CI = 68.29%) and chemical bonding within the material. Bacterial inhibition was identified from the antibacterial activity; this viable material is for applications in various engineering sectors, including construction, automotive, and aerospace industries.